PERLINDUNGAN HUKUM ATAS KARYAWAN ATAS PEMUTUSAN HUBUNGAN KERJA DI PT. HAIR STAR INDONESIA - Istighfariyo, M. Bagus; Simangunsong, Frans (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Termination of employment still become unsolved-well problems in many countries, especially in Indonesia whom the most crowded country in South East Asia. This case seen us how policy or political systems in Indonesia need improve and development in many sectors to provide mutual agreement for company and labour. Through Undang-Undang No.2 Tahun 2004 about Settlement of Industrial Relations Disputes, labour that were fired in PT. Hair Star Indonesia can be protected their rights. Conflict Resolutions through comprehensive methods, are the only answer to solving termination of employment problems in Indonesia